2015
DOI: 10.3390/cosmetics2010035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipids and Emulsifiers on the Physicochemical and Sensory Properties of Cosmetic Emulsions Containing Vitamin E

Abstract: Sensory properties are fundamental in determining the success of a cosmetic product. In this work, we assessed the influence of different oils and emulsifiers on the physicochemical and sensory properties of anti-ageing cosmetic O/W emulsions containing vitamin E acetate as active ingredient. No clear correlation between physicochemical properties and sensory characteristics was evidenced. Sensorial evaluation of these formulations pointed out that the emulsifier systems affected the perceived oiliness and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 26 publications
1
33
0
2
Order By: Relevance
“…17 The pH for newly formulated cosmetic products from natural clay material ranged from 4.94 for scrub to 6.97 for face mask, whereas in a published work, the pH of about 6.6 was reported for anti-ageing cosmetic emulsions containing vitamin E acetate as active ingredient. 18 Furthermore, these results agreed well with the pH of 6.6 obtained for emulsion cream that was formulated with natural plant extract. 19 The electrical conductivity of natural clay material was 315 µS cm -1 , this value was unexpectedly low in all cosmetic products including the control sample which indicated that all the samples were non-saline.…”
Section: Physicochemical Parameterssupporting
confidence: 82%
“…17 The pH for newly formulated cosmetic products from natural clay material ranged from 4.94 for scrub to 6.97 for face mask, whereas in a published work, the pH of about 6.6 was reported for anti-ageing cosmetic emulsions containing vitamin E acetate as active ingredient. 18 Furthermore, these results agreed well with the pH of 6.6 obtained for emulsion cream that was formulated with natural plant extract. 19 The electrical conductivity of natural clay material was 315 µS cm -1 , this value was unexpectedly low in all cosmetic products including the control sample which indicated that all the samples were non-saline.…”
Section: Physicochemical Parameterssupporting
confidence: 82%
“…The Polyacrylamide (and) C13-14 Isoparaffin (and) Laureth-7 polymer was the modifying agent with the greatest influence on the physico-mechanical properties of the developed formulations when the concentration varied without changing the other raw materials of (25,26) Todos os polímeros, com suas características estruturais, podem ajudar a melhorar as propriedades sensoriais; entretanto, o conhecimento sobre como os polímeros e suas concentrações podem influenciar as propriedades sensoriais é importante para a escolha correta dessas matérias-primas. (5) Por fim, considerando que existem poucos estudos relatados que avaliam as propriedades físico-mecânicas de formulações à base de polímeros, o presente estudo contribui para uma melhor compreensão do comportamento das matérias-primas adicionadas em formulações de uso tópico.…”
Section: Discussionunclassified
“…This characteristic is desired in cosmetic vehicles because of their high viscosity values, which implies a superior work of shear on skin, impairing the spreadability. (25,26) All polymers, with their structural characteristics, can help to improve sensorial proprieties; however, the knowledge about how polymers and their concentrations can influence the sensorial proprieties is important for the correct choice of these raw materials. (5) Finally, considering that there are a few studies reported to physico-mechanical properties of the formulation based on polymers, the present study is important for a better comprehension of raw materials on topical formulations.…”
Section: Análise Estatísticamentioning
confidence: 99%
“…Uji penerimaan dan preferensi menggunakan metode Montenegro et al (2015). Uji penerimaan dan preferensi digunakan untuk mengetahui penerimaan panelis terhadap ketujuh formulasi emulsi sarilabu kuning dan FO-MSM.…”
Section: Uji Penerimaan Dan Preferensi Panelisunclassified